ABC gene expression profiles have clinical importance and possibly form a new hallmark of cancer - Pavel Dvorak; Martin Pesta; Pavel Soucek (Tumor Biology)
Adenosine triphosphate–binding cassette proteins constitute a large family of active transporters through extracellular and intracellular membranes. Increased drug efflux based on adenosine triphosphate–binding cassette protein activity is related to the development of cancer cell chemoresistance. Several articles have focused on adenosine triphosphate–binding cassette gene expression profiles (signatures), based on the expression of all 49 human adenosine triphosphate–binding cassette genes, in individual tumor types and reported connections to established clinicopathological features. The aim of this study was to test our theory about the existence of adenosine triphosphate–binding cassette gene expression profiles common to multiple types of tumors, which may modify tumor progression and provide clinically relevant information. Such general adenosine triphosphate–binding cassette profiles could constitute a new attribute of carcinogenesis. Our combined cohort consisted of tissues from 151 cancer patients—breast, colorectal, and pancreatic carcinomas. Standard protocols for RNA isolation and quantitative real-time polymerase chain reaction were followed. Gene expression data from individual tumor types as well as a merged tumor dataset were analyzed by bioinformatics tools. Several general adenosine triphosphate–binding cassette profiles, with differences in gene functions, were established and shown to have significant relations to clinicopathological features such as tumor size, histological grade, or clinical stage. Genes ABCC7, A3, A8, A12 , and C8 prevailed among the most upregulated or downregulated ones. In conclusion, the results supported our theory about general adenosine triphosphate–binding cassette gene expression profiles and their importance for cancer on clinical as well as research levels. The presence of ABCC7 (official symbol CFTR ) among the genes with key roles in the profiles supports the emerging evidence about its crucial role in various cancers. Graphical abstract